2019
DOI: 10.1136/bmjopen-2019-029313
|View full text |Cite
|
Sign up to set email alerts
|

Orthotic management of instability of the knee related to neuromuscular and central nervous system disorders: qualitative interview study of patient perspectives

Abstract: ObjectivesAdults with knee instability related to neuromuscular disorders or central nervous conditions often experience mobility problems and rely on orthoses to improve function and mobility. Patient views of device effectiveness and acceptability are underexplored. Our study aimed to elicit device users’ perspectives regarding fitting, acceptability, effectiveness and use of orthoses, and identify important treatment outcomes.DesignQualitative descriptive study using in-depth semistructured interviews. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The topic "orthosis experience" therefore warrants further investigation in a prospective study. Nevertheless, our finding substantiates the results of a qualitative study that indicated a clear need for intensive support when first receiving an orthotic device, as people need time to adjust to an altered self-image (15), in addition to the practicalities of their KAFO in daily life, such as learning to operate the KAFO and adopting an efficient and functional gait pattern (24).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The topic "orthosis experience" therefore warrants further investigation in a prospective study. Nevertheless, our finding substantiates the results of a qualitative study that indicated a clear need for intensive support when first receiving an orthotic device, as people need time to adjust to an altered self-image (15), in addition to the practicalities of their KAFO in daily life, such as learning to operate the KAFO and adopting an efficient and functional gait pattern (24).…”
Section: Discussionsupporting
confidence: 87%
“…Amongst discontinued users, satisfaction was lowest for ease of use and comfort. Low satisfaction in terms of ease of use can imply problems with donning and doffing of the KAFO, which has been reported previously as a negative aspect of KAFO use in polio survivors (15) and individuals inclusion body myositis (29). Performing activities such as going up and down stairs, cycling or operating the KAFO may also result in low satisfaction with ease of use (28,30).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…One prior qualitative study of orthotic use by people with neuromuscular conditions (including some people with experiences of polio) has also highlighted the variability in outcome experiences from new orthotics -ranging from very positive to very negative (McCaughan et al, 2019). This prior study identified that any transition from an old to new orthotic could be challenging, making people reluctant to move to a new orthotic.…”
Section: Discussionmentioning
confidence: 99%